THE EFFECT OF RARE EARTH ELEMENTS ON Cr PRECIPITATIONS IN A Cu-0.8WT%Cr ALLOY - Shuai, Gewang; Zhang, Meng; Yan, Yongli (Image Analysis and Stereology, 2011)
The microstructural evolution of Cu-based alloys during aging was studied using a quantitative metallographic method. Samples were cut from ingots of Cu-0.8wt%Cr and Cu-0.8wt%Cr-RE alloys. These were solution treated at 1000 ºC for 1.5h and subsequently quenched in water, then separately aged at 480 ºC for different durations. The microstructures were observed by optical microscope, and the characteristic geometric parameters of precipitated Cr phase, including volume fraction VV, face density NA, mean diameter and roundness, were measured. These data provided more details about the process of aging. The results showed that precipitation of Cr phase occurred in the form of particles during aging. Rare earth elements promoted the precipitation of Cr phase and dispersed Cr particles. The phenomenon of overaging came earlier in Cu-Cr-RE than in Cu-Cr. In the present work, the optimal aging time at 480 ºC was 2 hrs for the Cu-0.8wt%Cr-RE alloy and 3 hours for the Cu-0.8wt%Cr alloy.